2010
DOI: 10.1124/mol.110.067512
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTION: A Novel Pentamethoxyflavone Down-Regulates Tumor Cell Survival and Proliferative and Angiogenic Gene Products through Inhibition of IκB Kinase Activation and Sensitizes Tumor Cells to Apoptosis by Cytokines and Chemotherapeutic Agents

Abstract: Most anticancer drugs have their origin in traditional medicinal plants. We describe here a flavone, 5,3Ј-dihydroxy-3,6,7,8,4Ј-pentamethoxyflavone (PMF), from the leaves of the Thai plant Gardenia obtusifolia, that has anti-inflammatory and anticancer potential. Because the nuclear factor-B (NF-B) pathway is linked to inflammation and tumorigenesis, we investigated the effect of PMF on this pathway. We found that PMF suppressed NF-B activation induced by inflammatory agents, tumor promoters, and carcinogens. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…They found that 5,3′‐dihydroxy‐3,6,7,8,4′‐pentamethoxyflavone induces apoptosis through multiple mechanism including down‐regulation of anti‐apoptotic factors (XIAP, cFLIP, Mcl‐1, Bcl‐2, and Bcl‐XL), induction of CDK inhibitors (p21 and p27), activation of caspases and inhibition of PI3K/AKT/GSK3β signaling . Moreover, 5,3′‐dihydroxy‐3,6,7,8,4′‐pentamethoxyflavone was found to sensitize cancer cell death caused by tumor necrosis factor‐α (TNF‐α) and chemotherapeutic drugs by targeting IKK and thus further abrogating the function of nuclear factor‐κB (NF‐κB) . 5,3′‐Dihydroxy‐3,6,7,8,4′‐pentamethoxyflavone was also reported to inhibit STAT3 activation not only through targeting multiple upstream kinases (JAK1, JAK2, Akt, and EGFR) but also through tyrosine phosphatase SHP‐1, which acts to de‐phosphorylate STAT3.…”
Section: Chemopreventive Effects Of Hydroxylated Pmfsmentioning
confidence: 99%
“…They found that 5,3′‐dihydroxy‐3,6,7,8,4′‐pentamethoxyflavone induces apoptosis through multiple mechanism including down‐regulation of anti‐apoptotic factors (XIAP, cFLIP, Mcl‐1, Bcl‐2, and Bcl‐XL), induction of CDK inhibitors (p21 and p27), activation of caspases and inhibition of PI3K/AKT/GSK3β signaling . Moreover, 5,3′‐dihydroxy‐3,6,7,8,4′‐pentamethoxyflavone was found to sensitize cancer cell death caused by tumor necrosis factor‐α (TNF‐α) and chemotherapeutic drugs by targeting IKK and thus further abrogating the function of nuclear factor‐κB (NF‐κB) . 5,3′‐Dihydroxy‐3,6,7,8,4′‐pentamethoxyflavone was also reported to inhibit STAT3 activation not only through targeting multiple upstream kinases (JAK1, JAK2, Akt, and EGFR) but also through tyrosine phosphatase SHP‐1, which acts to de‐phosphorylate STAT3.…”
Section: Chemopreventive Effects Of Hydroxylated Pmfsmentioning
confidence: 99%
“…Extracts of this plant are used to inhibit implantation (Luechtefeld et al, 1981) and suppress ulcers (Takase et al, 1989) and as an antibacterial agent (Laurens et al, 1985). One of the compounds isolated from this plant, 5, 6,7,8,, is cytotoxic to various cancer cell lines (Lichius et al, 1994;Shi et al, 1995;Zhang et al, 1999), exhibits anti-HIV activity (Tuchinda et al, 2004), is a potent inducer of apoptosis and abrogates the nuclear factor-B cell signaling pathway (Phromnoi et al, 2011). PMF isolated from another medicinal plant, Polanisia dodecandra (native to North America), has been reported to exhibit anticancer activity by binding to tubulin and inhibiting its polymerization (Lichius et al, 1994;Shi et al, 1995;Zhang et al, 1999).…”
Section: Introductionmentioning
confidence: 99%